2007
DOI: 10.1021/ma070523s
|View full text |Cite
|
Sign up to set email alerts
|

A Clathrate Form of Syndiotactic Poly(p-methylstyrene) Containing Two Different Types of Cavities

Abstract: The crystal structure of the clathrate form of syndiotactic poly(p-methylstyrene) containing benzyl chloride is presented. This structure presents a monoclinic unit cell (cell constants a ) 26.2 Å, b ) 11.8 Å, c ) 7.9 Å and γ ) 116°) in which the s(2/1)2 polymer helices and guest molecules are packed according the space group P2 1 /a. This molecular complex represents, to our knowledge, the first case of polymeric clathrate form in which in the same crystal are present two kinds of cavities having different sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Relevant new co-crystalline and nanoporous materials are expected in the future also for other stereoregular polymers that are able to form co-crystalline phases, like e.g. syndiotactic poly-p-methyl-styrene [110][111][112][113], syndiotactic poly-p-chloro-styrene [114], syndiotactic polymethyl-methacrylate [115], or polyethylene-oxide [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant new co-crystalline and nanoporous materials are expected in the future also for other stereoregular polymers that are able to form co-crystalline phases, like e.g. syndiotactic poly-p-methyl-styrene [110][111][112][113], syndiotactic poly-p-chloro-styrene [114], syndiotactic polymethyl-methacrylate [115], or polyethylene-oxide [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric cocrystalline forms are quite common for several regular and stereoregular polymers, such as, for example, isotactic21–23 and syndiotactic polystyrene (s‐PS),24–40 syndiotactic poly‐ p ‐methyl‐styrene,41–47 syndiotactic poly‐ m ‐methyl‐styrene,48, 49 syndiotactic poly‐ p ‐chloro‐styrene,50 syndiotactic poly‐ p ‐fluoro‐styrene,51 polyethyleneoxide,52–55 poly(muconic acid),56, 57 polyoxacyclobutane,58 poly(vinylidene fluoride),59, 60 syndiotactic polymethylmethacrylate,61–63 isotactic poly‐4‐methyl‐1‐pentene,64 or poly(2,6‐dimethyl‐1,4‐phenylene ether) (PPO) 65–68…”
Section: Cocrystalline Formsmentioning
confidence: 99%
“…This is because the pore size of sPPMS is larger than that of sPS because of the methyl group attached to phenyl ring in sPPMS. According to Tarallo et al, [32] the clathrate forms ofand -classes contain two and one guest molecules in the pore, respectively. They reported that nanoporous sPPMS cast-crystallized from o-xylene forms a -class clathrate.…”
Section: Number Of Phenol Molecules In the Pore Of Sppmsmentioning
confidence: 99%
“…The and class clathrates have a ttgg conformation with a period of 7.8 ± 0.1 Å. [29][30][31][32]The t6g2t2g2 conformation class clathrate has a period of 11.7 ± 0.1 Å. [33] A porous crystalline structure can be constructed in a crystal with the ttgg conformation by removing the solvent.…”
Section: Introductionmentioning
confidence: 99%